Preventing Poor Outcomes for Neurosurgical Patients - Klavansky, Dana; Kellner, Christopher; Ghatan, Saadi; Nelson, Sarah (Seminars in Neurology, 2022)
Ensuring that patients with neurosurgical conditions have the best possible outcome requires early diagnosis, monitoring, and interventions to prevent complications and optimize care. Here, we review several neurosurgical conditions and the measures taken to prevent complications and optimize outcomes. We hope that the practical tips provided herein prove helpful in caring for neurosurgical patients.
Keywords: neurosurgery; procedures; outcomes; neurocritical care